Pengaruh Citra Perusahaan dan Produk Bancassurance terhadap Perilaku Konsumen - Finny Ligery (Jurnal Studi Multidisiplin Ilmu, 2023)
Purpose: The study aims to know consumer behavior in the banking sector related to bancassurance products. This study input corporate image that play important role in the terms of providing information about bancassurance products that have low aspect according to the consumers’ perception. Method: This study is quantitative. The sample is taken by using purposive sampling from 200 consumers. The data was collected by using structural equation modeling by Lisler 8.8. Result: The results show that consumer behavior is influenced by corporate image and bancassurance products. It means the decision to buy is when the consumer knows that the banking party can be trusted and bancassurance products offered have advantages and profits. However, the banking image will be turned negative if bancassurance products offered to the consumers do not qualify as it was promised.